2020
DOI: 10.1177/2309499019895029
|View full text |Cite
|
Sign up to set email alerts
|

One-year follow-up of efficacy and cost of repeated doses versus single larger dose of intra-articular hyaluronic acid for knee osteoarthritis

Abstract: Purpose: A recent 3-month randomized, open-label controlled trial found that the intra-articular hyaluronic acid injection (GO-ON®) given as a single dose of 5 mL is as effective and safe as three repeated doses of 2.5 mL in patients with knee osteoarthritis. However, the information on the long-term efficacy and economic implications of the single-dose regimen is still limited. Hence, this follow-up study was designed to compare the effectiveness and costs of the two regimens 12 months following the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…We speculate that the short-term clinical outcomes were mainly affected by the enhancement of the microenvironment, immune-regulation and anti-inflammatory effects rather than cartilage regeneration itself, because cartilage regeneration would probably require a longer time to occur or would not happen even at longer follow up after MSC injections as described in several previous studies [18,33]. The efficacy of HA injections on pain relief and joint function restoration has been evaluated in numerous studies [10,19,26,40,41,51], and recent systematic reviews have shown that improvements in pain intensity and functional outcomes were likely to take effect in 4-8 weeks and could last up to 6 months [3,47]. Moreover, Suppan et al [51] suggested that HA efficacy was sustainable for ≥1 year.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We speculate that the short-term clinical outcomes were mainly affected by the enhancement of the microenvironment, immune-regulation and anti-inflammatory effects rather than cartilage regeneration itself, because cartilage regeneration would probably require a longer time to occur or would not happen even at longer follow up after MSC injections as described in several previous studies [18,33]. The efficacy of HA injections on pain relief and joint function restoration has been evaluated in numerous studies [10,19,26,40,41,51], and recent systematic reviews have shown that improvements in pain intensity and functional outcomes were likely to take effect in 4-8 weeks and could last up to 6 months [3,47]. Moreover, Suppan et al [51] suggested that HA efficacy was sustainable for ≥1 year.…”
Section: Discussionmentioning
confidence: 94%
“…Third, the optimal number of MSCs and dosage of HA remain unknown. Presently, low (0.5 × 10 6 –1 × 10 6 Da), intermediate (2 × 10 6 Da), or high (6 × 10 6 Da) molecular weights (MW) of HA are marketed; it is recommended to administer the low and intermediate MW of HA weekly for three to five doses, and the high MW of HA as a single larger dose [51]. In this study, high MW of HA was used.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, a single-injection IA HA therapy (3 mL, 60 mg) has been suggested as an alternative to the multi-injection regimen (currently 3 × 2 mL, 20 mg per injection), dispensing the same quantity of HA. A single injection would reduce the number of medical visits, intrusive procedures, and other associated risks [ 32 ]. HA increases the viscosity and elasticity of synovial fluid.…”
Section: Intra-articular Administration Of Therapeuticsmentioning
confidence: 99%
“…A more recent RCT by Suppan et al [ 44 ] compared single dose vs. repeated doses of HA injections and found that there was no significant difference between groups for pain scores up to 12 months. These results were corroborated by a recent 2019 meta-analysis of 28 studies, which concluded that single HA injections produced results comparable to those of multiple injections [ 45 ].…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…These results were corroborated by a recent 2019 meta-analysis of 28 studies, which concluded that single HA injections produced results comparable to those of multiple injections [ 45 ]. Because there is an approximately 30% lower cost associated with single-dose vs. multiple-dose regimes of HA, a single larger dose of HA is suggested as a future point of exploration [ 44 ].…”
Section: Hyaluronic Acidmentioning
confidence: 99%